Bilingual speech : a typology of code-mixing - Muysken, Pieter (Cambridge University Press, 2000)
"This book provides an in-depth analysis of the different ways in which bilingual speakers switch from one language to another in the course of conversation. This phenomenon, known as code-mixing or code-switching, takes many forms. Pieter Muysken adopts a comparative approach to distinguish between the different types of code-mixing, drawing on a wealth of data from bilingual settings throughout the world. His study identifies three fundamental and distinct patterns of mixing - 'insertion', 'alternation' and 'congruent lexicalization' - and sets out to discover whether the choice of a particular mixing strategy depends on the contrasting grammatical properties of the languages involved, the degree of bilingual competence of the speaker or various social factors. The book synthesises a vast array of recent research in a rapidly growing field of study which has much to reveal about the structure and function of language."--Jacket.